2015
DOI: 10.1111/os.12167
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Total Dislocation of the Talus

Abstract: This review summarizes the treatment and resulting outcomes for total talar dislocation. The PubMed database was searched for articles about humans with total talar dislocation published in the English language in the last twenty years. The following data were entered into a Microsoft Excel spreadsheet: type of dislocation, nature of associated fractures (if any), type of reduction/fixation utilized, immobilization, weight-bearing status, outcome, complications and average follow-up time. Thirty-nine articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 38 publications
(71 reference statements)
0
60
0
5
Order By: Relevance
“…An open type of dislocation and/or accompanying fracture is considered to be a risk factor with the possibility of an unfavorable outcome. 4 Taken together, we believe that confirming the presence of fractures by CT is critical in determining treatment strategy. In this case, an urgent closed reduction was successfully performed under general anesthesia using image guidance, and open fracture fixation was scheduled for the following day.…”
Section: Casementioning
confidence: 78%
See 1 more Smart Citation
“…An open type of dislocation and/or accompanying fracture is considered to be a risk factor with the possibility of an unfavorable outcome. 4 Taken together, we believe that confirming the presence of fractures by CT is critical in determining treatment strategy. In this case, an urgent closed reduction was successfully performed under general anesthesia using image guidance, and open fracture fixation was scheduled for the following day.…”
Section: Casementioning
confidence: 78%
“…The review showed that a good outcome was achieved in only 35% of cases and avascular necrosis was relatively common (26%) as a complication. An open type of dislocation and/or accompanying fracture is considered to be a risk factor with the possibility of an unfavorable outcome …”
Section: Casementioning
confidence: 99%
“…Weston and colleagues conducted a systematic review of total talar dislocation and identified infection development in 10 of 86 cases. 3 Smith and colleagues also found low infection rates in talus reimplantation after traumatic total dislocations with only 1 late infection from 27 patients. 4 The talus receives blood supply from the anterior and posterior tibial vessels, as well as perforating peroneal vessels and interosseous supply.…”
Section: Discussionmentioning
confidence: 94%
“…However, discarding the talus adversely affects hindfoot function and treatment should be focused on maximising function. 2 Avascular necrosis can occur anywhere between six months to two years after injury, with estimated rates of 26%, 3 although reports have shown successful reimplantation with no signs of avascular necrosis for at least four months at follow-up. 2,4 Post-traumatic osteoarthritis is another reported complication, with literature suggesting osteoarthritis development in 16% of open talar injuries.…”
Section: Discussionmentioning
confidence: 99%
“…50 % auf den Talushals, die restlichen Frakturen verteilen sich gleichsam auf Korpus sowie die Gelenkfortsätze [2]. Ursächlich sind insbesondere Verkehrsunfälle oder Stürze aus großer Höhe [3,4]. Wegen der großen knorpeligen Oberfläche des Talus (ca.…”
Section: Introductionunclassified